Prevalence and spectrum of hemoglobinopathies in tertiary care centre in a rural area of Madhya Pradesh - Nema, S. K.; Gupta, Mamta; Singh, Arjun; Jaiswal, S. S.; Kucheria, Mohini; Raipurkar, Swati (International Journal of Research in Medical Sciences, 2017)
Background: Haemoglobinopathies like thalassaemia and sickle cell anaemia etc are increasing due to unawareness of rural population. This study indicates type of haemoglobinopathies amongst the patients of a rural based tertiary care hospital in one year and nine months. Methods: Five hundred ten patients were studied during last one year and nine month for all suspected cases of haemolytic anaemia based on Complete Blood Count, Red cell indices and Peripheral blood smear examination. Sickling test, test for Hb F and haemoglobin electrophoresis with quantification of bands are done in all these cases Results: Out of all 510 cases of anaemia 461 cases (90.39%) were confirmed to nonhaemolytic anaemia whereas 49 cases (9.60%) had shown abnormal haemoglobin bands on electrophoresis. Out of these 49 cases 29 (59.18%) were Males and 20 (40.81%) were females. Most common Haemoglobinopathy observed was Sickle cell b Thalassaemia 23 (4.50%) followed by b Thalassaemia Trait 9 (1.76%), Sickle Cell trait 7 (1.37%). b Thalassaemia Major 5 (0.98%) & Sickle Cell Disease 5 (0.98%) have equal prevalence. The onset of disease was most prominent in Neonatal to pediatric age group including early adolescent (0-18 years) followed by reproductive age group (19- 45 years). Few cases of old age (46+ years) were detected. Conclusion: Study provides data on the spectrum & pattern of Haemoglobinopathies in a rural tertiary care centre. Screening of all anemic patients should be done for Haemoglobinopathy and proper Genetic counseling must be given to all cases to prevent incidence of cases in future generation.